Pengaruh Auditor Switching Terhadap Audit Report Lag: Studi Empiris pada Emiten property & real estate periode 2019-2023 - Inday Hardika; Sumarno Manrejo; Bambang Prayogo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to examine Auditor Switching on Audit Report Lag. The population in this study is all property & real estate sector companies listed on the Indonesia Stock Exchange in 2019-2023. The variables used in this study are Audit Report Lag as the dependent variable and Auditor Switching as independent variables. The sampling technique used was the purposive sampling method and obtained 95 company samples. The analysis methods used were Descriptive Statistical Analysis, Classical Assumption Test, Correlation Test, Multiple Linear Regression Test, and Hypothesis Test. The results showed that Auditor Switching had a significant positive effect on Audit Report Lag.